Study concerning the practice of physical exercises for recreational purposes - Aldea Elena; Florin LEUCIUC (Editura Univeristatii "Stefan cel Mare" din Suceava, 2024)
The concept of leisure was approached for the first time in Romania by M. Epuran and attributed this to the development of physical exercise practices in all social categories and age groups to cope with physical inactivity and excessive demands from occupational activities. The control group aims to emphasize the effectiveness of practicing physical exercises within the included physical education classes in the school curriculum, and in the research group we included students who participated in regular and organized activities in their free time. Based on the data collected on the physical activity of boys and girls, the level of development of psychomotor skills was assessed by using the following tests: 50-meter speed running, endurance running 800/1000 m, ball throwing, standing long jump, push-ups, trunk lifts, back extensions. The experimental group showed a better level of physical fitness at applied tests due the fact that practice more organized physical activity during the free time. Based on the results obtained in the research, taking into account the reason proposed in the elaboration of this work, we came to the conclusion that secondary school students from rural areas that practice physical exercises in their free time in an organized way and it becomes a habit for them to practice physical exercises independently and recreationally.